THE DYNAMICS OF THE CAPITAL MARKET: AN ANALYSIS OF PRE- AND POST-COVID-19 DEVELOPMENTS IN INDONESIA - Larkana Sari; Diyah Pujiati (Center for Indonesian Accounting Studies, 2025)
Research Objective - This research was conducted to test whether the government's announcement about Covid-19 was responded to by the capital market with the differences in abnormal returns and stock trading volume before and after the announcement. Methods - The research sample was 660 public companies, listed on the Indonesia Stock Exchange in 2020. The Wilcoxon sign rank test was used to test the research hypothesis, because the data was not normally distributed. Findings – Abnormal stock returns have been proven to have significant differences before and after the Covid-19 announcement. Even stock trading volume activity was shown the same result. The results show significant differences before and after the Covid-19 announcement. The test results for each sector show different abnormal returns before and after the announcement of Covid-19 in the various industries, consumer goods, and basic & chemical industries, while for trading volume activity there are differences only in the consumer goods sector. Theoretical and Policy Implications – The results can be used for decision making for policy makers to resolve the impact of the pandemic, especially on the sectors most affected by the pandemic. The research can also help potential investors in making investment decisions in the future. Research Novelty – This research was conducted on all companies listed on the Indonesian Stock Exchange in 2020 to see the impact of Covid-19 on the entire industrial sector due to the pandemic.